2014
DOI: 10.1242/bio.20147583
|View full text |Cite
|
Sign up to set email alerts
|

Smed-dynA-1 is a planarian nervous system specific dynamin 1 homolog required for normal locomotion

Abstract: Dynamins are GTPases that are required for separation of vesicles from the plasma membrane and thus are key regulators of endocytosis in eukaryotic cells. This role for dynamin proteins is especially crucial for the proper function of neurons, where they ensure that synaptic vesicles and their neurotransmitter cargo are recycled in the presynaptic cell. Here we have characterized the dynamin protein family in the freshwater planarian Schmidtea mediterranea and showed that it possesses six dynamins with tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…21 This suggests that the photoreceptor neurons or the transduction of their signals in the brain is not functioning correctly. Inhibition of genes involved in synaptic transmission 79,152,155 or neuropeptide processing also have profound effects on nervous system function. 51,156 Knockdown of Smed-pc2 impairs mobility 51,156 and disruption of dopaminergic signaling leads to severe locomotion defects.…”
Section: Recovering Function: Re-establishing Connections In the Cnsmentioning
confidence: 99%
“…21 This suggests that the photoreceptor neurons or the transduction of their signals in the brain is not functioning correctly. Inhibition of genes involved in synaptic transmission 79,152,155 or neuropeptide processing also have profound effects on nervous system function. 51,156 Knockdown of Smed-pc2 impairs mobility 51,156 and disruption of dopaminergic signaling leads to severe locomotion defects.…”
Section: Recovering Function: Re-establishing Connections In the Cnsmentioning
confidence: 99%
“…Decreases in motility have been found in adult flatworms acutely exposed to MDL-12,330A (Matsuyama et al 2004), mianserin (Currie and Pearson 2013;Talbot et al 2014;Chan et al 2016;Shettigar et al 2021), sertraline (Thumé and Frizzo 2017;Weeks et al 2018), and high concentrations of caffeine (Best and Morita 1982;Moustakas et al 2015). Previous studies on the effects of caffeine in planarians have only found behavioral effects at much higher concentrations than we tested here (mM instead of µM).…”
Section: Hts Can Recapitulate Findings From Low-throughput Studiesmentioning
confidence: 57%
“…Acute exposure to mianserin has previously been shown to induce muscle-based movement in Schmidtea mediterranea planarians (Currie and Pearson 2013; Talbot et al 2014). Our finding that low to mid-concentrations of mianserin cause a significant induction of muscle waves suggests that mianserin acts similarly in D. japonica .…”
Section: Discussionmentioning
confidence: 99%